Особенности в работе систем источника мощности – генератора многократных токовых импульсов - Аргун, Щасяна Валиковна (НТУ "ХПИ", 2013)
Проведен анализ схемных решений по подключению инструмента магнитно-импульсного воздействия к источнику мощности. Раскрыты особенности построения системы контроля и управления магнитно-импульсной установки в режиме многократных токовых импульсов. Приведено описание структурных схем системы контроля и управления.

An analysis of circuit designs as to connecting a magnetic pulse action tool to a power source has been carried out. Design features of a magnetic pulse installation control and monitoring system in a multiple current pulse mode have been revealed. The description of the control and monitoring system block diagrams has been presented.
Working features of power source systems – a multiple current pulse generator
Keywords: магнитно-импульсные установки; генераторы токовых импульсов; обработка металлов; коммутирующие устройства; источники мощности; magnetic-pulse metal working; magnetic pulse installation; monitoring and control system; thyristors; unipolar pulse